Identifikasi Jenis Zooplankton di Sepanjang Perairan Sungai Jangkok Kota Mataram - Safnowandi, Safnowandi (Biocaster : Jurnal Kajian Biologi, 2024)
Zooplankton is animal plankton, which plays a role as primary consumers in aquatic ecosystems and as a link in the aquatic food chain. The Jangkok River is one of the large rivers on Lombok Island. This river flows from the western slopes of Mount Rinjani through the Narmada area of ​​West Lombok Regency to downstream at Ampenan Beach. Many river flows provide functions and benefits for the continuity of life of the surrounding community. This research aims to identify zooplankton in the waters of the Jangkok River, Mataram City. This type of research is exploratory descriptive. Research procedures include taking zooplankton water samples horizontally and vertically. Data collection techniques use observation and documentation techniques. The data analysis technique uses the zooplankton abundance index. The research results show that there are 4 types of Zooplankton consisting of 4 species that have been discovered including Harpacticoid copepod, Parathemisto abyssorum, Cyclops bicuspidatus and Diaptomus sp.